2022
DOI: 10.1111/geoj.12438
|View full text |Cite
|
Sign up to set email alerts
|

Student loneliness through the pandemic: How, why and where?

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited and is not used for commercial purposes. The information, practices and views in this article are those of the author(s) and do not necessarily reflect the opinion of the Royal Geographical Society (with IBG).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 39 publications
0
14
0
Order By: Relevance
“…The percentage of respondents who selected each practice increased from 2018 to 2021. One possible explanation could be the COVID-19 pandemic, which caused many students to feel socially isolated and perhaps strengthened their desire to be connected to people and places (Smith et al 2022).…”
Section: Student Survey Resultsmentioning
confidence: 99%
“…The percentage of respondents who selected each practice increased from 2018 to 2021. One possible explanation could be the COVID-19 pandemic, which caused many students to feel socially isolated and perhaps strengthened their desire to be connected to people and places (Smith et al 2022).…”
Section: Student Survey Resultsmentioning
confidence: 99%
“…Scholarly research indicates that there has been a surge in the prevalence of loneliness among college and university-level students across various academic levels since the onset of the outbreak (Phillips et al, 2022 ). Conversely, senior individuals have exhibited heightened resilience to the psychological ailments associated with pandemic-induced living conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, being able to share one's meal without digitally connection, while considering this a satisfactory meal would protect against loneliness. Phillipps et al. ’s (2022) study of students during lockdowns reported that students valued being able to share meals regularly with their roommates compared to those who could not.…”
Section: Discussionmentioning
confidence: 99%